2022
DOI: 10.1001/jamaoncol.2022.1479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supine vs Prone Breast Radiotherapy on Acute Toxic Effects of the Skin Among Women With Large Breast Size

Abstract: IMPORTANCEWomen with large breast size treated with adjuvant breast radiotherapy (RT) have a high rate of acute toxic effects of the skin. Breast RT in the prone position is one strategy that may decrease these toxic effects.OBJECTIVE To determine if breast RT in the prone position reduces acute toxic effects of the skin when compared with treatment in the supine position.DESIGN, SETTING, AND PARTICIPANTS This phase 3, multicenter, single-blind randomized clinical trial accrued patients from 5 centers across C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…A previous BC Cancer randomized trial to investigate potential advantages of silver leaf nylon dressing to promote wound healing found that 38% of breast RT patients with D cup or larger, or with skin folds 1 cm or deeper, experienced MD at our institution [ 11 ]. This is consistent with a recent randomized controlled trial of prone breast RT for a similar patient population [ 8 ]. Skin-sparing techniques such as partial breast irradiation and hypo-fractionated breast RT treatment schedules have reported lower rates of acute skin toxicity in intact breast RT [ 8 , 12 , 13 ].…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…A previous BC Cancer randomized trial to investigate potential advantages of silver leaf nylon dressing to promote wound healing found that 38% of breast RT patients with D cup or larger, or with skin folds 1 cm or deeper, experienced MD at our institution [ 11 ]. This is consistent with a recent randomized controlled trial of prone breast RT for a similar patient population [ 8 ]. Skin-sparing techniques such as partial breast irradiation and hypo-fractionated breast RT treatment schedules have reported lower rates of acute skin toxicity in intact breast RT [ 8 , 12 , 13 ].…”
Section: Introductionsupporting
confidence: 92%
“…This is consistent with a recent randomized controlled trial of prone breast RT for a similar patient population [ 8 ]. Skin-sparing techniques such as partial breast irradiation and hypo-fractionated breast RT treatment schedules have reported lower rates of acute skin toxicity in intact breast RT [ 8 , 12 , 13 ]. Other interventions such as a novel carbon-fiber breast support to remove infra-mammary folds (IMFs) are also under investigation for reduction in MD rates [ 14 ].…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations